Уровень антител к антигенам вируса Эпштейна—Барр как дополнительный критерий при определении онкологического риска у пациентов с хроническими заболеваниями желудка или легких - Кузнецова, Т.И.; Уразова, Л.Н.; Коломиец, С.А.; Карасева, В.В. (Онкологія, 2001)
Изучены возможности использования иммунного ответа на антигены вируса Эпштейна—Барр (ВЭБ) у лиц с хроническими заболеваниями желудка (ХЗЖ) и хроническими неспецифическими заболеваниями легких (ХНЗЛ) при проведении ранней диагностики неоплазий. С помощью реакции непрямой иммунофлюоресценции сыворотки крови обследованы 254 пациента с ХЗЖ, 256 — с ХНЗЛ. При сравнительном анализе ВЭБ-специфического иммунитета пациентов с хроническими заболеваниями и здоровых лиц было установлено, что среднегеометрические титры антител к антигенам ВЭБ у больных достоверно превышали аналогичные показатели у здоровых лиц. В течение 3 лет наблюдения у 9 пациентов с ХНЗЛ и у 3 — с ХЗЖ с аномально высоким уровнем ВЭБ-специфических антител диагностированы злокачественные новообразования соответствующих локализаций. На основании полученных данных сформулированы критерии для формирования групп повышенного риска по изученным локализациям. The aim of this research was to study the feasibility of using immune responses to Epstein—Barr virus (EBV) antigens in patients with chronic gastric and pulmonary diseases in early cancer detection. Samples of blood sera from 254 patients with chronic gastric diseases (CGD) and 256 patients with chronic non-specific pulmonary diseases (CNPD) were tested for the presence of specific antibodies to EBV antigens (capsid and early antigen complexes) using the method of indirect immunofluorescence. As a result, it was shown that all the patients examined were infected with EBV. A comparative analysis of EBV-specific immunity showed that the mean geometric titers (MGT) of antibodies to this virus in patients with chronic diseases were significantly higher than those observed in healthy subjects (p < 0.001). Cancer was detected within a 3-year follow-up period in 9 patients with CNPD and in 3 patients with CGD. All these patients were found to have abnormally high levels of EBV-specific antibodies. Thus, it can be assumed that testing for the presence of immunovirological markers can be used as a helpful additional test in the formation of the groups at risk for EBV-associated malignant tumors.